PENGARUH PROFITABILITAS, STRUKTUR ASET, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Nabilla Ayuningtyas, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence about the effects of profitability, asset structure, firm size, and liquidityoncapital structurein manufacturing industries listed in Indonesian Stock Exchange during the period of 2015-2017. This research used 66samples of manufacturing companies that have been previously selected using purposive sampling method for three years. The data used were secondary data in the form of financial information from the financial statements and annual reports. This research data was processed using EViews 10. The result of this research shows that liquidity has an effect on capital structure, while profitability, asset structure,and firm size does not have an effect on capital structure. Suggestion that can be given for the future research is to use other independent variables, such as non-debt tax shield.